Better urban services : finding the right incentives. (Washington, D.C. : World Bank, 1995)
This book uses the lessons from lending for urban development to build a conceptual framework that can guide the process of improving service delivery. This framework looks beyond local governments alone as the cause of poor performance and points toward reforming the incentives they face. Key issues examined include clarifying the division of functional responsibilities between levels of government, making revenue sources correspond to functional responsibilities, and putting in place a governmental system that balances central regulation with local incentives to respond to constituents - all of which especially pertain to the many countries undertaking decentralization. This book seeks to begin a global dialog on how urban services delivery can be improved and to serve as a catalyst for further learning from the rich experience of administrative reform under way in many developing countries.
"Modified version of a document that was reviewed by the Board of Executive Directors of the World Bank in September 1994".
Includes bibliographical references (p. 81-84).
oif 11/02/15
Loan
Keywords: World Bank -- Developing countries; Urban development -- Developing countries; Intergovernmental fiscal relations -- Developing countries; Municipal services -- Developing countries; Decentralization in government -- Developing countries